The Breeding Ecology of the Red-Billed Tropicbird (Phaethon aethereus) within a Productivity Gradient: Evaluating the Impact of Local Conditions on Body Size and Foraging Ecology - Piña Ortiz, Alberto; Justus Liebig University Giessen (My University, 2024)
The environment plays a central role in shaping the biology of marine life at different scales and ecosystems. Factors such as wind, temperature, salinity, pH levels, topography and nutrient availability affect the behaviour, distribution and adaptation of marine organisms, influencing their physiology, behavioural patterns and life-history strategies. Therefore, this thesis investigates how local environmental conditions (e.g. air temperature, sea surface temperature, chlorophyll-a, bathymetry) affect the body size and foraging ecology (behaviour and diet) of the Red-billed Tropicbird (Phaethon aethereus) along a productivity gradient in the Mexican Pacific, in order to understand how the environment influences the biology of this seabird and how it adjusts its phenotype, behaviour and diet in response to local conditions. The body size variation and sexual size dimorphism (SSD) in colonies of red-billed tropicbirds along a productivity gradient in the Mexican Pacific are evaluated (Chapter 1). The species shows phenotypic plasticity with an increase in body size from south to north (1-9%), correlated with environmental productivity. SSD is only present in two northern colonies, where males are larger than females. The SSD detected in colonies with larger body sizes, together with high chlorophyll-a values and low sea surface temperature values, suggests that environment-mediated body size variation is a crucial factor in SSD. Tracking data combined with stable isotope values (δ15N and δ13C), and observations of parental nest presence, meal size and chick feeding events, show that breeding adults employ a bimodal foraging strategy as soon as the chick hatches, and that the parental duties of offspring care and provisioning are clearly linked to the foraging behaviour of the species during this stage (Chapter 2). A comparative assessment of the feeding ecology of the species, through analysis of faecal (DNA metabarcoding) and blood (stable isotopes) samples, between sites located in systems of contrasting productivity, revealed that the species exhibits trophic plasticity based mainly on the consumption of mesopelagic and epipelagic offshore fish (Chapter 3). Furthermore, variation in diet between sites is influenced by the abundance and composition of prey present in each system, and fluctuations throughout the breeding season are linked to prey availability due to changes in local oceanographic conditions, as well as to the energetic demands that adults must satisfy according to their breeding stage. Overall, this research highlights the phenotypic and trophic plasticity of red-billed tropicbirds, as well as their foraging behaviour. These aspects are influenced by environmental factors, demonstrating that this interaction is fundamental to the species' ecology. The findings contribute to a better understanding of the species' ecology, specifically its foraging behaviour, feeding habits, and evolution. The information from this dissertation is expected to be useful for developing current or future marine management plans that promote sustainable use of marine resources, while considering habitat protection and the conservation of biological components.
Keywords: Body-size cline; Local Environmental conditions; Phenotypic plasticity; Sexual size dimorphism; Bimodal foraging; Foraging behavior; GPS-tracking; Parental duties; Stable isotopes; Dietary plasticity; Feeding strategy; Gulf of California; Mexican Tropical Pacific; Red-billed Tropicbird; ddc:570; ddc:590; ddc:500